Intussusception in a child with situs inversus totalis - A rare occurrence - Alex Osei Assim; Robert Sagoe; Anwar Sadat Seidu; Edwin Saanwie (Elsevier, 2022)
Intussusception is when section of bowel is drawn into another. It is considered the commonest cause of intestinal obstruction in children. It is associated with a favorable outcome when diagnosis and management are prompt. Non-operative management techniques are employed in most cases with surgical reduction occurring in a third of cases. Situs anomalies are a rare spectrum of congenital anomalies involving malpositioning of the thoracoabdominal viscera. Situs inversus totalis is the commoner of the subdivision of the situs inversus spectrum. The condition is associated with several anomalies including, katagener's syndrome. Its association with intestinal obstruction is however extremely rare. There is no known reported case of intussusception occurring in a child with situs inversus totalis. Here, we report a case of seven (7) months old female diagnosed with intussusception and situs inversus totalis following clinical and radiological evaluation. She underwent open reduction and Ladd's procedure and made an uneventful recovery.